Ease of Doing Business and Economic Growth: A Panel Analysis of Selected Sub-Sahara African Countries (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
Entrepreneurship emerges as a catalyst for growth and advancement through production and trade. This work jointly examines the influence of ease of doing business and worldwide governance indicators on economic growth of selected SSA countries from 2010 to 2020. Adopting an empirical approach, the study tries to ascertain this relationship using a random effect panel regression model and Kao co-integration estimation. A balanced panel consisting of Forty one (41) out of forty eight (48) countries were selected for the analysis. Eight (8) variables out of eleven (11) ease of doing business indicators, and three (3) out of six (6) governance indicators were selected for the study. They were chosen based on their appropriateness for the research according to the authors instincts and prevalent challenges bedeviling Sub-Saharan African countries. We identify a positive significant relationship between getting credit and economic growth, while a negative association between political stability and regulatory requirement. The study recommends greater access to finance for businesses, especially small and medium enterprises (SMEs), and capacity building among others, as one of the ways to maximize the dividends of local and international trades across the region. Sub-Saharan governments should establish a robust evaluation and monitoring framework to catalyze the success of policy interventions.